Volatile composition and contribution to the aroma of Spanish honeydew honeys. Identification of a new chemical marker - Castro-Vazquez, L; Diaz-Maroto, M C; Perez-Coello, M S (JOURNAL OF AGRICULTURAL AND FOOD CHEMISTRY, 2006)
Honeydew honeys from holm-oak, oak, and forest were isolated for aroma compounds by simultaneous distillation-extraction and analyzed by gas chromatography-mass spectrometry. In all, 66 volatile components were identified and quantified. trans-Oak lactone, a characteristic volatile component of oak wood, is proposed as a new chemical marker for the plant origin of honeydew honeys. Other compounds, such as aminoacetophenone and propylanisol, could be considered characteristic of holm-oak honeydew honeys. A total of 15 volatile compounds presented odor activity values (OAVs) greater than 1, with phenylacetaldehyde and beta-damascenone being those with the highest OAVs.
Keywords: aroma; gas chromatography; honey; honeydew honey; volatile compounds